Third Culture Kids, their diversity beliefs and their intercultural competences - de Waal, Monika F.; Born, Marise Ph; Brinkmann, Ursula; Frasch, Jona J.F. (International journal of intercultural relations, 2020)
Positive diversity beliefs are known to increase the effectiveness of diverse groups in organizations and society. Early cross-cultural experiences might facilitate developing these diversity beliefs. This study examined the relationship between being a third-culture kid (TCK) and one’s diversity beliefs, and the possible mediation of this relationship by intercultural competences. Data came from 1454 respondents, 17–19 years of age, who filled out the Intercultural Readiness Check (IRC) between 2011 and 2016 (49.1 % female, 50.9 % male). 65.0 % of the respondents had specified their nationality as Dutch, and 35.0 % had indicated a different nationality. 550 respondents (37.8 %) had spent one or more years abroad and were thus classified as TCKs. Their diversity beliefs were compared to 904 respondents (62.2 %) who had never lived abroad, and who therefore were classified as non-TCKs. A mediated regression analysis showed that TCKs had higher positive diversity beliefs than non-TCKs, and that this relationship was mediated by the degree to which they had developed specific intercultural competences, being intercultural sensitivity and building commitment. These findings show that early cross-cultural life experiences help individuals to develop intercultural competences and positive diversity beliefs. Equipped with these competences and beliefs, TCKs can add value to organizations and society.